Cancel Culture - Asiki, Katerina; Lioliou, Nefeli (Open Schools Journal for Open Science, 2025)
This presentation explores the phenomenon of cancel culture, examining its definition, historical roots, connection to social media, and its dual roles as both activism and a threat to free speech. It analyzes public opinions and outlines the consequences of cancel culture, including case studies of Korean celebrities. The goal is to provide a balanced view of this complex cultural trend.